Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

My lecturer in his notes uses this definition of Poisson distribution:

$$ P_{X}(t)= \exp( \lambda (t-1)) $$

You differentiate once and set equal $t=1$ to get $E[X]=\lambda$, but in the notes to get $E[X^2]$, he doesn't differentiate $P_{X}(t) = \exp( \lambda (t-1))$ twice and set equal $t=1$.

Instead the formulae used is this $E[X^2-X]=P_{X}''(1)$.

Can someone explain that? As it confusing the hell out of me. Like I don't know when to just differentiate twice and make it equal to $E[X^2]$ or I have to do that trick.

Or maybe you can't actually differentiate twice to get $E[X^2]$.

share|cite|improve this question
Take a look at factorial moments and factorial moment generating functions (That's what he's using). – Mike Wierzbicki Nov 4 '11 at 1:22
@Mike Oh thanks that makes perfect sense now. – simplicity Nov 4 '11 at 1:24
up vote 4 down vote accepted

The formula $P_X(t)$ is your notes is the factorial moment generating function, defined as $$ P_X(t) = \mathbb{E}( t^X ) $$ Therefore: $$ P_X^\prime(t) = \mathbb{E}(X t^{X-1} ) \qquad P_X^{\prime\prime}(t) = \mathbb{E}(X (X-1) t^{X-2} ) \qquad P_X^{(k)}(t) = \mathbb{E}( X(X-1) \cdots (X-k+1) t^{X-k} ) $$ Setting $t=1$ afterwords makes $t^{X-k}$ factor equal 1 and you are left with expectations of linear combination of moments. Thus $$ m_1 = P^\prime(1) \qquad m_2 = P_X^{\prime\prime}(1) + P_X^\prime(1) \qquad m_k = \sum_{m=0}^k \mathsf{S}^{(2)}_{k,m} P_X^{(m)}(1) $$ where $\mathsf{S}^{(2)}_{k,m}$ is the Stirling number of the second kind.

share|cite|improve this answer
What is this approach called? I may look some similar approach somewhere. Maybe is it the connection between factorial moment generating function and moment generating function? – Fan Zhang Nov 4 '11 at 3:00
@FanZhang Yes, this is exactly that. Notice that $P_X(\exp(u)) = M_X(u)$, where $M_X$ is the moment generating function. – Sasha Nov 4 '11 at 3:55

If you were thinking about the moment generating function rather than the factorial moment generating function it would look like this:

$M_{X}(t)=\exp( \lambda (e^t-1))$ is the moment generating function of a Poisson distribution, not $\exp( \lambda (t-1))$.

Differentiate it once to $M'_{X}(t)=\lambda \exp(\lambda (e^t-1)+t)$ and set $t=0$ (not $1$) to get $E[X]=M'_{X}(0)=\lambda$.

Differentiate it again to $M''_{X}(t)=\lambda^2 \exp(\lambda (e^t-1)+2t)+\lambda \exp(\lambda (e^t-1)+t)$ and set $t=0$ to get $E[X^2]=M''_{X}(0)=\lambda^2+\lambda$.

So $\operatorname{Var}(X)=E[X^2]-(E[X])^2=\lambda^2+\lambda-\lambda^2=\lambda$ as expected.

share|cite|improve this answer
As Sasha points out, you are not using the moment generating function, but I will leave this here anyway as it may be of interest to somebody. $M_X(t)$ is the usual notation for the moment generating function – Henry Nov 4 '11 at 1:37

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.